Stres Oksidatif di dalam Model Kerja Obat Antimalaria - Syamsudin Syamsudin (Fakultas Farmasi Universitas Pancasila, 2006)
Several antimalarial drugs may act by producing free radicals, anion superoxide through a redox cycling process with oxygen. The mode of action of chloroquine, primaquine, artemisinin, anthraquinone and xanthones as antimalarial drug is partly increasing the oxidative stress in the parasitized red blood cell.